2021
DOI: 10.1016/j.jbc.2021.101326
|View full text |Cite
|
Sign up to set email alerts
|

The intrinsic kinase activity of BRD4 spans its BD2-B-BID domains

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…This is also similar to the reported results on BRD4-T and was observed for BRDT-T here as well. We believe that the intrinsically disordered region connecting the BDs largely contributes to a higher affinity for dsDNA. , This has also been postulated before as the linker is rich in basic residues and has an A-motif (281–300), which is speculated to phosphorylate the Pol II C-terminal domain (CTD) via direct engagement, though nothing is known about its structure …”
Section: Discussionmentioning
confidence: 54%
“…This is also similar to the reported results on BRD4-T and was observed for BRDT-T here as well. We believe that the intrinsically disordered region connecting the BDs largely contributes to a higher affinity for dsDNA. , This has also been postulated before as the linker is rich in basic residues and has an A-motif (281–300), which is speculated to phosphorylate the Pol II C-terminal domain (CTD) via direct engagement, though nothing is known about its structure …”
Section: Discussionmentioning
confidence: 54%
“…Interestingly, BET family proteins have been identified as atypical kinases, which might affect gene transcription also by alternative mechanisms [42]. For example, Brd4 may affect gene transcription by phosphorylation of transcription machinery [43]. Brd4 possesses intrinsic kinase activity and may directly phosphorylate RNA polymerase II, TATA-box binding protein associated factor 7 (TAF7), and positive transcription elongation factor b/cyclin-dependent kinase 9 (PTEFb/CDK9) [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, several residues from MLV-EBM, including L399, I401, V392, L403, and W390, are positioned within the hydrophobic core of the ET domain ( Figure 11 D). In addition to the NMR experiments, affinity pull-down experiments further support that the acidic and hydrophobic residues of the ET domain are critical for the binding and potentially linked to its phosphorylation [ 174 , 192 , 202 ]. Based on the solved structure model, Xing et al [ 203 ] reported that 399 LKIRL 403 is a critical amino acid (or hot-spot) sequence that carries out the MLV-EBM/Brd4-ET interactions.…”
Section: Targeting At the Extra-terminal (Et) Domain Of Brd4mentioning
confidence: 99%